Analisis Harga Satuan Pekerjaan Jalan dan Jembatan Menggunakan Program Lazarus (studi kasus devisi 3, 5, 6, & 7) - Trisno Imany, Tri Subakti; Hadi, Yohannes Martono; Zakaria, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
In the activity construction work must be would related to the cost. Someone who estimate the budget construction cost is called estimator. An estimate of the cost was called unit price analysis of work. Most of unit price analysis still was counted manually , but if seen from various points of view , calculations conducted in the manual still cannot meet its demands availability of information a quick and accurate. Therefore needs to get a program automatically for can count quickly unit price analysis.To observe a unit price of work so fast and accurated can be making an application analysis using the lazarus and than becomparations with the method of analysis issued by ministry of public worksThe result of making program unit price analysis of work of using lazarus is tested and validated by calculation use secondary data issued by ministry of public works. By using this program the calculations be more effective when compared with calculate by hand. Keywords: Unit price analysis, Lazarus